2020
DOI: 10.1016/j.jcot.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Is obesity A contra-indication for a successful total knee arthroplasty?

Abstract: Background: Total Knee Arthroplasty (TKA) is one of the most effective treatment modalities for chronic knee pain and disability. A strong association exists between obesity and early knee osteoarthritis. Various studies on outcomes of TKA in obese patients have been inconclusive. The purpose of this retrospective evaluation is to assess the influence of obesity on outcomes of TKA in Indian patients. Methods: This retrospective study conducted from 2010 to 2016 included 402 knees in 213 patients with Body Mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…Similar results have been reported by Amin et al [14], patients where obese patients undergoing TKA had similar outcomes compared to non-obese patients. In our retrospective series of 402 TKA in 213 patients, we have observed that functional scores and complication rates in obese patients are comparable to the historical control of non-obese patients [21].…”
Section: Discussionsupporting
confidence: 51%
“…Similar results have been reported by Amin et al [14], patients where obese patients undergoing TKA had similar outcomes compared to non-obese patients. In our retrospective series of 402 TKA in 213 patients, we have observed that functional scores and complication rates in obese patients are comparable to the historical control of non-obese patients [21].…”
Section: Discussionsupporting
confidence: 51%
“…Similarly, we found that increased body mass index was an important feature predictive of persistent opioid use after lower extremity arthroplasty. This can be secondary to limitation to the progression of inpatient rehabilitation postoperatively36 or pharmacokinetics, however, outcomes and complications in obese patients are comparable to non-obese patients 37–39…”
Section: Discussionmentioning
confidence: 99%
“…This can be secondary to limitation to the progression of inpatient rehabilitation postoperatively 36 or pharmacokinetics, however, outcomes and complications in obese patients are comparable to non-obese patients. 37–39 …”
Section: Discussionmentioning
confidence: 99%
“…Another study found no difference in outcomes for patients who have Class 1 or Class 2 obesity compared with patients who are not obese [3], so should we concentrate on exploring these relationships just in patients with BMIs over 40 kg/m 2 , over 45 kg/m 2 , or over 50 kg/m 2 [21]?…”
Section: How Do We Get There?mentioning
confidence: 99%
“…There are many avenues to explore: Some studies have shown that more experience with doing TKA in patients with morbid obesity leads to shorter operative times and fewer adverse postoperative outcomes [14, 23]. Another study found no difference in outcomes for patients who have Class 1 or Class 2 obesity compared with patients who are not obese [3], so should we concentrate on exploring these relationships just in patients with BMIs over 40 kg/m 2 , over 45 kg/m 2 , or over 50 kg/m 2 [21]?…”
Section: How Do We Get There?mentioning
confidence: 99%